A mu SR study of the CDW in TTF-TCNQ - Marshall, I; Pratt, F; Blundell, S; Husmann, A; Hayes, W; Sugano, T (2001)
The muon spin rotation (mu SR) technique is primarily a powerful probe of the magnetic properties of materials; but it is also possible to measure charge-density related effects using muon quadrupolar level crossing resonance (QLCR). We present the first study of a charge density wave (CDW) using mu SR in TTF-TCNQ. The CDW develops below the metal-insulator transition at 54 K and we study the evolution of the CDW as a function of temperature using the QLCR resonances of the nitrogen atoms on the TCNQ molecules as the probe.